Optimization Of Customized Tetra-Flute Drill Reamer For A Better Hole Quality In Single Shot Drilling Of Cfrp Composite Laminate - Choo, Then Xiang (Universiti Sains Malaysia, 2021)
Carbon fibre reinforced polymer (CFRP) is a popular material that used in the aerospace and automotive industries in recent years. The drilling process is typically involved in the manufacture of CFRP products and a drill with a good design can help the manufacturing industry to reduce waste of energy, material and money. To obtain a good drill reamer, drill geometry such as drill diameter, helix angle, clearance angle and point thickness were investigated by collecting data based on five responses, namely thrust force, diameter error, surface roughness, delamination and wear analysis. Based on Regression analysis, thrust force, surface roughness and wear analysis have higher variability to perform a deeper analysis, which is the interaction plot that used to analyse the relationship between the four factors in these three single responses. Nine customized drill reamers that are separated into three categories, which are drill diameters of 3.20 mm, 4.85 mm and 6.35 mm, were used in the research. Those drill reamers were used to drill the CFRP workpiece afterwards. Through this research, it was found that the four factors, which are the drill diameter, helix angle, clearance angle and point thickness, would have different level of impact on certain response. The response values for the thrust force, diameter error, surface roughness, delamination and the wear analysis obtained through the research also differ with various parameters combinations of parameters. At the end of the research, the optimum parameters for customized tetra-flute drill reamer to perform one shot drilling of CFRP to obtain better hole quality was Run A1 (3.20 mm), Run B2 (4.85 mm) and Run C1 (6.35 mm). While the parameters combinations for Run A1 is helix angle (0º), clearance angle (9º) and point thickness (15%). While the parameters combination for Run B2 is helix angle (5º), clearance angle (9º) and point thickness (20%) whereas Run C1 are helix angle (0º), clearance angle (12°) and point thickness (20%).